2011
DOI: 10.1631/jzus.b1100061
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of seed germination under salt stress in soybeans

Abstract: Soybean (Glycine max (L.) Merrill) is a salt-sensitive crop, and its production is severely affected by saline soils. Therefore, the response of soybean seeds to salt stress during germination was investigated at both physiological and proteomic levels. The salt-tolerant cultivar Lee68 and salt-sensitive cultivar N2899 were exposed to 100 mmol/L NaCl until radicle protrusion from the seed coat. In both cultivars, the final germination percentage was not affected by salt, but the mean germination times of Lee68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 48 publications
(50 reference statements)
2
50
0
2
Order By: Relevance
“…Detam-3, Seulawah, Merbabu, Gumitir, Ichiyou, and Petek delayed germination but did not reach one day. Xu et al (2011) reported that 100 mMolal.L -1 NaCl decreases MGT value. Farhoudi and Tafti (2011) and Taufiq and Purwaningrahayu MGT is average time of germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detam-3, Seulawah, Merbabu, Gumitir, Ichiyou, and Petek delayed germination but did not reach one day. Xu et al (2011) reported that 100 mMolal.L -1 NaCl decreases MGT value. Farhoudi and Tafti (2011) and Taufiq and Purwaningrahayu MGT is average time of germination.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, salinity is known to delay germination time (Xu et al 2011;Taufiq and Purwaningrahayu 2013;Kandil et al 2015). Soybean germination percentage decreases significantly with increasing levels of saline.…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination is a complex process involving biochemical and physical activities [1,40]. Hydrolytic enzymes are activated after the imbibition of water and decompose large molecular substances of reserve compounds such as starch, non-starch polysaccharides, and proteins in the endosperm, leading to increases in small molecular compounds such as glucose, oligosaccharides and amino acids in germinated seeds [1,2,41].…”
Section: Discussionmentioning
confidence: 99%
“…Besides ionic and osmotic effects, which are the primary stresses of salinity, high salt concentrations additionally induce secondary stresses such as oxidative stress due to the excessive generation of ROS [40,42,43]. To prevent oxidative damage, plants process both enzymatic mechanisms such as APX and CAT, and non-enzymatic mechanisms such as phenolic compounds for ROS scavenging [7,8,43].…”
Section: Discussionmentioning
confidence: 99%
“…Over 20 50% of the whole arable land is affected by salt stress every year (Xu et al, 2011). Salinity decreases the productivity of most crops as plant growth is affected in several aspects of its metabolism.…”
Section: Introductionmentioning
confidence: 99%